Integrated and iterative systems engineering and software requirements engineering for technical systems. Issue 9 (16th May 2016) - Holtmann, Jörg; Bernijazov, Ruslan; Meyer, Matthias; Schmelter, David; Tschirner, Christian
Abstract: The development of software‐intensive technical systems involves several engineering disciplines like mechanical, electrical, control, and particularly software engineering. Model‐based Systems Engineering (MBSE) coordinates these disciplines throughout the development by means of discipline‐spanning processes and a system model. Such a system model provides a common understanding of the system under development and serves as a starting point for the discipline‐specific development. An integral part of MBSE is the requirements engineering on the system level. However, these requirements need to be refined for the discipline‐specific development to start, for example, into specific requirements for the embedded software. Because existing MBSE approaches lack support for this refinement step, we conceived in previous work a systematic transition from MBSE to model‐based software requirements engineering. We automated the steps of the transition where possible, in order to avoid error‐prone and time‐consuming manual tasks. In this paper, we extend this approach with support for subsequent process iterations and provide an algorithm for the automated steps. We illustrate the approach and perform a case study with an example of an automotive embedded system. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The development of software‐intensive technical systems involves several engineering disciplines. Model‐based systems engineering (MBSE) coordinates these disciplines throughout the development by means of a discipline‐spanning system model. An integral part of MBSE is the requirements engineering on the system level. However, these requirements need to be refined for the discipline‐specific development to start, for example, into specific requirements for the embedded software. In this paper, we present a systematic, semi‐automatic, and iterative transition from MBSE to model‐based software requirements engineering.